2018
DOI: 10.1038/s41598-018-25727-8
|View full text |Cite|
|
Sign up to set email alerts
|

DRP-1-mediated apoptosis induces muscle degeneration in dystrophin mutants

Abstract: Mitochondria are double-membrane subcellular organelles with highly conserved metabolic functions including ATP production. Mitochondria shapes change continually through the combined actions of fission and fusion events rendering mitochondrial network very dynamic. Mitochondria are largely implicated in pathologies and mitochondrial dynamics is often disrupted upon muscle degeneration in various models. Currently, the exact roles of mitochondria in the molecular mechanisms that lead to muscle degeneration rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 111 publications
(130 reference statements)
4
8
0
Order By: Relevance
“…However, our data do not show the hyper-connected phenotype previously observed with RNAi knockdown of drp - 1 [ 21 , 24 ]. Instead, our findings support those of Ackema et al who demonstrated differences in mitochondrial morphology when drp - 1 was knocked down versus knocked out, with blebs rather than hyper-connection the predominant phenotype in animals carrying the drp - 1(tm1108) null allele [ 27 , 28 ]. This blebbing phenotype has been proposed to result from fission of the inner mitochondrial membrane still occurring in the absence of DRP-1 [ 24 , 28 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, our data do not show the hyper-connected phenotype previously observed with RNAi knockdown of drp - 1 [ 21 , 24 ]. Instead, our findings support those of Ackema et al who demonstrated differences in mitochondrial morphology when drp - 1 was knocked down versus knocked out, with blebs rather than hyper-connection the predominant phenotype in animals carrying the drp - 1(tm1108) null allele [ 27 , 28 ]. This blebbing phenotype has been proposed to result from fission of the inner mitochondrial membrane still occurring in the absence of DRP-1 [ 24 , 28 ].…”
Section: Resultssupporting
confidence: 91%
“…These findings are, however, consistent with recent studies in C. elegans that have also not observed hyper-connected mitochondria when using genetic knockouts [ 5 , 27 ]. Ackema et al demonstrated that the absence of DRP-1 in fact causes the formation of blebs in the mitochondrial network, which may be a consequence of fission of the inner mitochondrial membrane still occurring in the absence of DRP-1 [ 24 , 27 , 28 ]. In mammalian cells, and in concert with DRP1, the dynamin-2 protein was recently shown to drive the final constriction event required for mitochondrial division [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the possible underlying mechanisms behind the loss of muscle strength in dystrophin mutants, we looked at the integrity of the mitochondrial network of dys-1(cx18) and dys-1(eg33) animals that had been crossed with the CB5600 strain, which expresses GFP in the mitochondria and nuclei of the body wall muscles. Recently, Scholtes et al (2018) reported mitochondrial fragmentation as a phenotype of their sensitized muscular dystrophy strain, dys-1; hlh-1 . Here, we report that mitochondrial network integrity is also compromised in dys-1(cx18) and dys-1(eg33) compared with wild-type animals of the same age, with the defect in dys-1(eg33) being more severe (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has also recently been found that dystrophin-dependent muscle degeneration is quickly followed by an increase in mitochondria fragmentation and apoptosis. Decreasing mitochondrial fission by inhibiting drp-1 (mitochondrial fission gene) or ced-3 (cleaves DRP-1) or increasing mitochondrial fusion by overexpressing eat-3 or fzo-1 (inner and outer mitochondrial membrane fusion, respectively) in the dys-1(cx18);hlh-1(cc561) model results in a reduction in mitochondrial fragmentation and fewer abnormal muscle cells [27]. In addition to altering mitochondrial dynamics, inhibiting genes involved in apoptosis and DNA degradation could be a potential treatment for DMD.…”
Section: Mitochondrial Genesmentioning
confidence: 99%
“…In addition to altering mitochondrial dynamics, inhibiting genes involved in apoptosis and DNA degradation could be a potential treatment for DMD. The inhibition of wah-1 (orthologue of human AIF), cps-6 (orthologue of human EndoG), crn-2 (orthologue of human TATDN1), ced-1 (cell-corpse recognition), and psr-1 (migration of engulfing cells) in dys-1(cx18);hlh-1(cc561) also caused a decline in the number of abnormal muscle cells, suggesting that they all participate in cell death upon dystrophin-muscle degeneration [27].…”
Section: Mitochondrial Genesmentioning
confidence: 99%